Análise de grelhas com elementos de eixo curvo e seção variável: aplicação ao cálculo de linhas de influência em vigas curvas - Figueirôa, José do Patrocínio (1972)
In the present thesis plane grids with curved members of uniform and non-uniform cross-sections are analysed using matrix techniques. An available program proposed by Gere and Weaver has been extended to analyse them. The author develops a second program for the determination of influence lines in curved beams composed of circular segments, with elastic suports. In the first part of the thesis the theory of curved members with variable cross-section is reviewed. In the second part FORTRAN listings of the two programs are presented and some applications to practical problems.